Intrinsic effect of interfacial coupling on the high-frequency intralayer modes in twisted multilayer MoTe2. Issue 21 (21st May 2021) - Leng, Yu-Chen; Lin, Miao-Ling; Zhou, Yu; Wu, Jiang-Bin; Meng, Da; Cong, Xin; Li, Hai; Tan, Ping-Heng
Abstract : The out-of-plane intralayer modes in twisted multilayer MoTe2 are sensitive to its interfacial layer-breathing coupling, while the in-plane intralayer modes are localized within its constituents due to the negligible shear coupling at the interface. Abstract : The interfacial coupling at the interface makes the van der Waals heterostructures (vdWHs) exhibit many unique properties that cannot be realized in its constituents. Such a study usually starts with a twisted stack of two flakes exfoliated from the same layered materials to form twisted multilayers, in which the impact of interfacial coupling on the low-frequency interlayer modes had been well understood. However, it is not clear how interfacial coupling affects the high-frequency intralayer modes of twisted multilayers. Herein, we perform high-resolution resonance Raman spectroscopy of the high-frequency intralayer modes in twisted multilayer MoTe2 (tMLM). All the Davydov entities of the out-of-plane intralayer mode are observed and distinguished at 4 K. It is found that the out-of-plane intralayer modes in tMLM are sensitive to its interfacial layer-breathing coupling so that the out-of-plane intralayer modes in tMLM do not show a direct relationship with those of the two constituents. However, the case is quite different for the in-plane intralayer modes in tMLM, whose spectral profile can be fitted by those of the corresponding modes of its constituents. This indicates that the in-plane intralayer modes are localized within the constituents in tMLM because of its negligible interfacial shear coupling at the interface. All the results can be well understood using the vdW model in which only the nearest neighbor interlayer/interfacial interaction is taken into account. This work directly builds the relationship between the Davydov splitting of the high-frequency intralayer vibrations and the low-frequency interlayer vibrations in tMLM, which can be further extended to other twisted materials and the related vdWHs.